Delivering health : midwifery and development in Mexico - Dixon, Lydia Zacher, 1980- (Policy to practice (Nashville, Tenn.), 2020)
"This book, based on seventeen months of ethnographic research on midwifery education in Mexico, illustrates the ways that midwives work both with and against the state as they confront poor maternal conditions that represent a legacy of inequality and violence"--